Optimalisasi Peran Karang Taruna Dalam Mengembangkan Desa Wisata Melalui Pelatihan Desain Grafis Media Gawai (Studi Kasus Pada Desa Prajegan Kecamatan Sukorejo) - Azis, Latif Saiful; Setyawan, Agus (Social Science Academic, 2024)
Prajegan village is one of the villages in the Sukorejo sub-district, known as a tourist village; it has 6 hamlets with tourism potential in different fields of art. This research aims to discover Karang Taruna's role in their participation in developing Prajegan Village as a Tourist Village, especially through social media. The research method uses the ABCD approach through interviews and field observations of the Prajegan Village Heads, Karang Taruna, and the Prajegan Village Community research subjects. The result of this research is to develop creativity and overcome the boredom of Karang Taruna members through graphic design training using mobile media. From this activity, Karang Taruna's creativity in social media will increase so that the role in supporting the development of the Prajegan Tourist Village becomes better.